Proceedings of the 2022 Annual ACM-SIAM Symposium on Discrete Algorithms (SODA) 2022
DOI: 10.1137/1.9781611977073.4
|View full text |Cite
|
Sign up to set email alerts
|

Learning-Augmented Weighted Paging

Abstract: We consider a natural semi-online model for weighted paging, where at any time the algorithm is given predictions, possibly with errors, about the next arrival of each page. The model is inspired by Belady's classic optimal offline algorithm for unweighted paging, and extends the recently studied model for learning-augmented paging [45,50,52] to the weighted setting.For the case of perfect predictions, we provide an -competitive deterministic and an O(log )-competitive randomized algorithm, where is the number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…Algorithms with predictions. Many recent studies [36,41,4,34,43,2,5] improved competitive ratios of online algorithms with predictions. Dinitz et al [17] proposed to warm-start algorithms with predictions.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Algorithms with predictions. Many recent studies [36,41,4,34,43,2,5] improved competitive ratios of online algorithms with predictions. Dinitz et al [17] proposed to warm-start algorithms with predictions.…”
Section: Related Workmentioning
confidence: 99%
“…Since such instances arising in the same domain often have some tendencies, using predictions made from past instances to improve algorithms' performance is a natural and promising idea. A recent line of work [36,41,4,34,43,2,5] successfully combined online algorithms with predictions and showed that those algorithms perform provably better than known worst-case bounds if predictions are good while enjoying worst-case guarantees even if predictions are poor. See [37] for a survey.…”
Section: Introductionmentioning
confidence: 99%
“…The online version has applications to the design and analysis of hybrid algorithms. In particular, the disjoint paths case has applications in derandomizing online algorithms [20], in the design of divide-and-conquer online algorithms [19,2], and in the design of advice and learning augmented online algorithms [25,1,5]. In this context, Kao et al [23] resolve exactly the randomized competitive ratio of width 2 layered graph traversal: it is roughly 4.59112, precisely the solution for in the equation ln( − 1) = −1 ; see also [13].…”
Section: Introductionmentioning
confidence: 99%
“…Width layered graph traversal includes as a special case metrical task systems in -point metric spaces. 5 There is a tight bound of 2 − 1 on the deterministic competitive ratio of metrical task systems in any -point metric [9], and the randomized competitive ratio lies between an Ω(log /log log ) lower bound (Bartal et al [6,7]) and an (log 2 ) upper bound (Bubeck et al [10]). Thus, width layered graph traversal is strictly a more general problem than -point metrical task systems.…”
Section: Introductionmentioning
confidence: 99%
“…Further related work There has been signi cant interest in the recent framework of learning-augmented online algorithms. Many problems have been considered, e.g., caching [49,55,4], further scheduling [36,8,7,56,10,44,45,50], rent-or-buy problems [48,24,2,12,54,5,56], paging [33,23,13], graph problems [22,9,57,39], secretary problems [6,20], matching [4,37,38] and many more.…”
Section: Introductionmentioning
confidence: 99%